2018
DOI: 10.1534/g3.118.200072
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II Transcription Attenuation at the Yeast DNA Repair Gene, DEF1, Involves Sen1-Dependent and Polyadenylation Site-Dependent Termination

Abstract: Termination of RNA Polymerase II (Pol II) activity serves a vital cellular role by separating ubiquitous transcription units and influencing RNA fate and function. In the yeast Saccharomyces cerevisiae, Pol II termination is carried out by cleavage and polyadenylation factor (CPF-CF) and Nrd1-Nab3-Sen1 (NNS) complexes, which operate primarily at mRNA and non-coding RNA genes, respectively. Premature Pol II termination (attenuation) contributes to gene regulation, but there is limited knowledge of its prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 105 publications
(154 reference statements)
2
19
0
Order By: Relevance
“…The prematurely terminated transcripts sometimes initiate at a TSS upstream of the protein-coding gene [102] . Interestingly, it was recently shown that the DNA repair gene DEF1 is attenuated by Sen1 and CPA factors, without Nrd1 and Nab3 involvement [106] ; therefore, PTT in S. cerevisiae might not be limited to the NNS pathway. There are no Nrd1/Nab3 homologues known in plants.…”
Section: Transcriptional Control By Premature Termination: Revisitedmentioning
confidence: 99%
“…The prematurely terminated transcripts sometimes initiate at a TSS upstream of the protein-coding gene [102] . Interestingly, it was recently shown that the DNA repair gene DEF1 is attenuated by Sen1 and CPA factors, without Nrd1 and Nab3 involvement [106] ; therefore, PTT in S. cerevisiae might not be limited to the NNS pathway. There are no Nrd1/Nab3 homologues known in plants.…”
Section: Transcriptional Control By Premature Termination: Revisitedmentioning
confidence: 99%
“…Interestingly, it was recently shown that the DNA repair gene DEF1 is attenuated by Sen1 and CPA factors, without Nrd1 and Nab3 involvement [95], therefore PTT in S. cerevisiae might not be limited to the NNS pathway.…”
Section: Ptt In Bacteria Yeast and Plantsmentioning
confidence: 99%
“…snRNAs, snoRNAs, cryptic unstable transcripts) ( Arndt and Reines 2015 ). Our laboratory more recently characterized an attenuator in the DNA repair gene DEF1 that relies on CF, CPF, and Sen1 without apparent involvement of Nrd1/Nab3, suggesting that yeast attenuation is not constrained to NNS ( Whalen et al 2018 ). We referred to the DEF1 attenuation mechanism as “hybrid” termination, recognizing that others have documented similar CPF-CF and NNS crosstalk in 3′-end gene regions as part of a failsafe mechanism ( Lemay and Bachand 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We initially identified the yeast DNA repair gene DEF1 as an attenuation target based on its usage of both promoter-proximal and promoter-distal pA sites ( Graber et al 2013 ; Whalen et al 2018 ). DEF1 encodes a protein essential for the degradation of Pol II stalled at UV-induced DNA lesions, which provides DNA repair factors with access to their substrate ( Akinniyi and Reese 2021 ).…”
Section: Introductionmentioning
confidence: 99%